2017
DOI: 10.4236/ojn.2017.79075
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Improving Nursing Handoffs in Surgical Wards

Abstract: Objective: To propose approaches to improve nursing handoffs for surgical patients, including standardization. Background: Handoffs, or the transfer of accountability and patient information, can generate potential risks for patient safety. Standardization has been proposed to help improve handoffs. Methods: After observing 333 nursing handoffs in the surgical wards of our institution, we conducted a thematic content analysis, comparing and contrasting the observations. Results: Handoff processes, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…These characteristics also emerged as one of the four major groups of the cluster analysis. The nursing handover process provides the opportunity to reinforce the cohesion of the nurses as a group and the professional socialization, training, interaction and emotional support of group members (18)(19) . Therefore, the handover must be precise, complete, specialized, relevant and, above all, based on objective criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics also emerged as one of the four major groups of the cluster analysis. The nursing handover process provides the opportunity to reinforce the cohesion of the nurses as a group and the professional socialization, training, interaction and emotional support of group members (18)(19) . Therefore, the handover must be precise, complete, specialized, relevant and, above all, based on objective criteria.…”
Section: Discussionmentioning
confidence: 99%
“…emerged were that the information presented was based on nursing diagnoses and therefore appeared to operate on the basis of best nursing clinical practice (18) . The same study found that nurses used clinical handover.…”
Section: Descriptoresmentioning
confidence: 99%